Urelumab alone or in combination with rituximab in patients with relapsed or refractory B‐cell lymphoma - Timmerman, John; Herbaux, Charles; Ribrag, Vincent; Zelenetz, Andrew D.; Houot, Roch; Neelapu, Sattva S.; Logan, Theodore; Lossos, Izidore S.; Urba, Walter; Salles, Gilles; Ramchandren, Radhakrishnan; Jacobson, Caron; et al. (American journal of hematology, 2020)
Urelumab, a fully human, non‐ligand binding, CD137 agonist IgG4 monoclonal antibody, enhances T‐cell and natural killer‐cell antitumor activity in preclinical models, and may enhance cytotoxic activity of rituximab. Here we report results in patients with relapsed or refractory diffuse large B‐cell lymphoma (DLBCL), follicular lymphoma (FL), and other B‐cell lymphomas, in phase 1 studies evaluating urelumab alone (NCT01471210) or combined with rituximab (NCT01775631). Sixty patients received urelumab (0.3 mg/kg IV Q3W, 8 mg IV Q3W, or 8 mg IV Q6W); 46 received urelumab (0.1 mg/kg, 0.3 mg/kg, or 8 mg IV Q3W) plus rituximab 375 mg/m2 IV QW. The maximum tolerated dose (MTD) of urelumab was determined to be 0.1 mg/kg or 8 mg Q3W after a single event of potential drug‐induced liver injury occurred with urelumab 0.3 mg/kg. Treatment‐related AEs were reported in 52% (urelumab: grade 3/4, 15%) and 72% (urelumab + rituximab: grade 3/4, 28%); three led to discontinuation (grade 3 increased AST, grade 4 acute hepatitis [urelumab]; one death from sepsis syndrome [urelumab plus rituximab]). Objective response rates/disease control rates were 6%/19% (DLBCL, n = 31), 12%/35% (FL, n = 17), and 17%/42% (other B‐cell lymphomas, n = 12) with urelumab and 10%/24% (DLBCL, n = 29) and 35%/71% (FL, n = 17) with urelumab plus rituximab. Durable remissions in heavily pretreated patients were achieved; however, many were observed at doses exceeding the MTD. These data show that urelumab alone or in combination with rituximab demonstrated manageable safety in B‐cell lymphoma, but the combination did not enhance clinical activity relative to rituximab alone or other current standard of care.